Comparative Analysis of Chloroplast Genome and New Insights Into Phylogenetic Relationships of Polygonatum and Tribe Polygonateae - Wang, Jing; Qian, Jun; Jiang, Yuan; Chen, Xiaochen; Zheng, Baojiang; Chen, Shilin; Yang, Fajian; Xu, Zhichao; Duan, Baozhong (Frontiers in Plant Science, 2022)
Members of Polygonatum are perennial herbs that have been widely used in traditional Chinese medicine to invigorate Qi, moisten the lung, and benefit the kidney and spleen among patients. However, the phylogenetic relationships and intrageneric taxonomy within Polygonatum have long been controversial because of the complexity of their morphological variations and lack of high-resolution molecular markers. The chloroplast (cp) genome is an optimal model for deciphering phylogenetic relationships in related families. In the present study, the complete cp genome of 26 species of Trib. Polygonateae were de novo assembled and characterized; all species exhibited a conserved quadripartite structure, i.e., two inverted repeats (IR) containing most of the ribosomal RNA genes, and two unique regions, LSC (large single sequence) and SSC (small single sequence). Eight highly variable regions (rps16-trnQ-UUG, trnS-GCU-trnG-UCC, rpl32-trnL-UAG, matK-rps16, petA-psbJ, trnT-UGU-trnL-UAA, accD-psaI, and trnC-GCA-petN) that might be useful as potential molecular markers for identifying Polygonatum species. The molecular clock analysis results showed that the divergence time of Polygonatum might occur at ~14.71 Ma, and the verticillate leaf might be the ancestral state of this genus. Moreover, phylogenetic analysis based on 88 cp genomes strongly supported the monophyly of Polygonatum. The phylogenetic analysis also suggested that Heteropolygonatum may be the sister group of the Polygonatum, but the Disporopsis, Maianthemum, and Disporum may have diverged earlier. This study provides valuable information for further species identification, evolution, and phylogenetic research of Polygonatum.